User Generated Content and Generation Z Tourists’ Visit Intention: Evidence from the Newly Inaugurated Kebumen Geopark, Indonesia - Apidana, Yordan Hermawan; Prasetyo, Anton; Kholifah, Kholifah (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study examines the influence of user-generated content on Generation Z tourists’ visit intention toward Geopark Kebumen through the Stimulus Organism Response framework. Emotional and factual user-generated content were conceptualized as external stimuli affecting trust in user-generated content and the destination image as organismic states, which, in turn, influence visit intention as the response. A quantitative approach was applied using Partial Least Squares Structural Equation Modeling, based on 315 valid responses from active social media users aged 17–28 years. Results show that emotional content significantly enhances destination image, trust, and visit intention, while factual content affects destination image and trust but has no direct influence on intention. Trust in user-generated content emerges as the strongest predictor of both destination image and visit intention, confirming its central role as a cognitive-affective bridge in the decision process. The findings validate the Stimulus Organism Response framework for digital tourism behavior and emphasize the importance of authenticity, emotional resonance, and credibility in shaping Generation Z travel decisions. The study contributes to theory development in digital destination marketing and provides managerial insight for promoting geotourism through authentic, emotionally engaging, and trustworthy user-generated content.